The Advantages and Disadvantages of Introducing a New User-Generated Content Exception Into Copyright Legislation (Asian Journal of Social Science Studies, 2022)
User-generated content (UGC) has arose many arguments while thriving. It is important but difficult to keep a balance between encourage creation and tolerance of light infringement in the field of UGC. Introducing a new exception for UGC maybe a proper method to keep the balance which may lead uncertainty and lack of protection. On contrary, a future compulsory-licensing approach may play a better role to keep the balance. Compulsory-licensing poor provide right holder a platform to sharing their content and gain profits according to the policy of sharing economy. Besides, it also enables right holder to drop out from this sharing pool when the right holder aims to control the copyright as much as possible. This new licensing method can protect the copyright as well as encouraging the prosperity of UGC industry.